2016
DOI: 10.2215/cjn.07680715
|View full text |Cite
|
Sign up to set email alerts
|

Educating Patients about CKD

Abstract: Patient education is associated with better patient outcomes and supported by international guidelines and organizations, but a range of barriers prevent widespread implementation of comprehensive education for people with progressive kidney disease, especially in the United States. Among United States patients, obstacles to education include the complex nature of kidney disease information, low baseline awareness, limited health literacy and numeracy, limited availability of CKD information, and lack of readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(214 citation statements)
references
References 93 publications
2
205
1
6
Order By: Relevance
“…The specific factors contributing to this gap are complex, but certainly 7,9 include lack of patient disease awareness and self-advocacy 247 . Research has shown that disease awareness in patients with CKD stages 1–3 is as low as 5% even in patients that have seen a physician within the last year 247250 . Physicians may neglect mentioning to patients the fact that they have kidney disease, perhaps in part because they don’t believe they can offer effective therapeutic options.…”
Section: Challenges In the Development Of Novel Therapies For Chronicmentioning
confidence: 99%
“…The specific factors contributing to this gap are complex, but certainly 7,9 include lack of patient disease awareness and self-advocacy 247 . Research has shown that disease awareness in patients with CKD stages 1–3 is as low as 5% even in patients that have seen a physician within the last year 247250 . Physicians may neglect mentioning to patients the fact that they have kidney disease, perhaps in part because they don’t believe they can offer effective therapeutic options.…”
Section: Challenges In the Development Of Novel Therapies For Chronicmentioning
confidence: 99%
“…In addition, there may be no reliable partner for home‐based therapies . Patient‐related factors may include much comorbidity, belief they would be better off in a hospital, fear of self‐cannulation (in home hemodialysis), limited health literacy, and as many patients do not have consistent predialysis care by a nephrologist, lack of awareness about home‐based therapies . It is with these patient‐related factors that public health strategies within a community may be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…34 In Cuba, the Ministry of Public Health has implemented a national programme for the prevention of CKD. Narva et al 43 found that patient education is associated with better patient outcomes. There has been an increased rate of the diagnosis of diabetes and of glycaemic control, as well as an increased diagnosis of patients with hypertension, higher prescription use of renoprotective treatment with angiotensin converting enzyme inhibitor and higher rates of blood pressure control.…”
Section: A Rational Approach To Ckd Early Detectionmentioning
confidence: 99%